Death and burial in ancient Egypt - Ikram, Salima (American university, 2015)
Death, burial, and the afterlife were as important to the ancient Egyptians as how they lived. This well-illustrated book explores all aspects of death in ancient Egypt, including beliefs of the afterlife, mummification, the protection of the body, tombs and their construction and decoration, funerary goods, and the funeral itself. It also addresses the relationship between the living and the dead, and the magico-religious interaction of these two in ancient Egyptian culture.Salima Ikram's own experience with experimental mummification and funerary archaeology lends the book many completely original and provocative insights. In addition, a full survey of current development in the field makes this a unique book that combines all aspects of death and burial in ancient Egypt into one volume.